Effect of Conceptual Scaffolding in the E-Recitation Program on Students Conceptual Understanding - Fartin Wendra; Nehru Nehru; Cicyn Riantoni (Jurnal Pijar MIPA, 2026)
Conceptual understanding is a fundamental aspect of physics learning because each concept is interrelated and becomes the basis for mastering subsequent materials. However, students often experience misconceptions that lead to low conceptual mastery. This study aims to analyze the effect of conceptual scaffolding in the E-Recitation program on students' conceptual understanding of temperature and heat. This study uses a quantitative, experimental approach with a One-Group Pretest-Posttest Design, which involves a single group without a control group. The research subjects were 29 grade XI Science students. The research procedure consisted of three main stages: administering a pretest to measure students' initial abilities, providing treatment by implementing conceptual scaffolding in the E-Recitation program, and administering a posttest to measure changes in conceptual understanding after treatment. The instrument used was a conceptual understanding test comprising 20 multiple-choice questions, validated by experts. The data were analyzed using the Shapiro-Wilk normality test followed by a paired sample t-test to test the hypothesis, as well as to calculate the effect size. The average pretest score of 55.00 increased to 77.24 in the posttest. The analysis results indicate that the data are normally distributed, and the paired-samples t-test is significant (p = 0.000 < 0.05), indicating a significant difference between the pretest and posttest results. In addition, the effect size of 2.07 falls in the very large category. The novelty of this study lies in the direct application of conceptual scaffolding to each answer choice through guiding questions and conceptual feedback videos in the E-Recitation system. Thus, it can be concluded that the application of conceptual scaffolding in the E-Recitation program has a very significant effect on improving students' conceptual understanding of temperature and heat.